Exploring EFL Students' Reading Comprehension Process through Their Life Experiences and the Sight Word Strategy - Jennifer Camargo; Jenny Carolina Orbegozo Navarro (Asociación Colombiana de Profesores de Ingles, 2010)
Due to the role language and literature play in the construction of social, economic and cultural systems, reading comprehension has become a growing challenge. This study examined how the relationship between English as a foreign language reading comprehension and life experiences while using the Sight Word Strategy could prove significant. Fifth graders at a public school in Bogotá participated in this study. Data were collected using tape recordings, field notes, archival data and students' reflections. Analysis indicated that comprehension and construction of meaning were generated by sharing life experiences and through the interaction produced in each one of the Sight Word Strategy stages. The study suggested further research into a more encompassing definition of reading comprehension and life experiences correlation as an appropriate goal for English as a foreign language.